INTEGRASI BUDAYA DAN AGAMA: KETERLIBATAN ANAK DALAM TRADISI BABALIAN SEBELUM WALIMATUL ‘URSY DALAM PERNIKAHAN DI NAGARI PARIANGAN PERSPEKTIF HUKUM - Zulfa Marlina; Nofialdi Nofialdi; Dodon Alfiander; Siska Elasta Putri (UIN Mahmud Yunus Batusangkar, 2022)
This study examines the background of children's involvement in the implementation of the babalian tradition before walimatul 'ursy in marriage from the perspective of Islamic law. From these problems, the question arises what is the background to the involvement of children in the babalian tradition before walimatul 'ursy in marriage. This study is based on field research. The data were obtained through interviews and then the data were narrated descriptively. The results achieved are to find out the background of the child's involvement in the babalian tradition, namely 1) the child is a symbol of descent and is also a basarayo tampek (person who will be ordered around), because ideally, the person who will be ordered is smaller than the person who ordered. 2) In addition, this tradition does not violate the Shari'a, because even though it is carried out at night, children are free to follow this series of traditions or choose to rest. This child also gets supervision from parents and adults. So it can be said that this tradition is 'urf authentic because it does not conflict with Islamic law and there is no harm to the child